The Dynamics of Implicit Intergroup Biases of Victims and Ex-combatants in Post-conflict Scenarios - Baez, Sandra (Journal of interpersonal violence, 2022)
Strong group identities arise in intergroup conflict scenarios and perpetuate sectarian violence even in post-conflict scenarios. In particular, out-group negative implicit associations are predictors of decreased intergroup forgiveness, as well as increased distrust and aggression against the out-group. Thus, the presence of implicit intergroup (i.e., ex-combatants and victims) biases seems to be a relevant factor in post-conflict scenarios. Here, we aimed to explore whether negative biases toward the out-group are boosted by (a) previous exposure to conflict violence or (b) identification with an armed violent group. One hundred and twenty-eight participants, 65 ex-combatants from Colombian guerrillas and 63 victims of the armed conflict, were assessed with a modified version of the implicit association test (IAT). Our results revealed that the victim group showed a significant negative bias against ex-combatants. However, no bias toward the out-group (i.e., victims) or in-group favoritism was observed in the ex-combatant group. Similarly, we found that IAT scores were not associated with sociodemographical variables (i.e., sex, years of education, or type of dwelling), the levels of combat exposure, victimization armed-conflict-related experiences, or child abuse antecedents. Our results showed an unexpected lack of in-group bias in ex-combatants, potentially triggered by the effect of current demobilization and reintegration processes. Thus, negative associations with the out-group will persist in the framework of societal condemnation of the out-group. In contrast, these negative biases will tend to be abolished when entering in conflict with larger societal reintegration processes. The results reinforce the idea that reintegration may benefit from interventions at the societal level, including all actors of the conflict. In addition, our findings highlight the importance of implementing victim interventions aimed at reducing stigma and revengeful actions in spaces of collective disarmament.